Dietary Habits and Nutrition Knowledge among Athletes and Non-Athletes in National University of Malaysia (UKM) - Sedek, Razalee; Yih, Tan Yun (Pakistan Journal of Nutrition, 2014)
Nutrition knowledge is vital in determining the pattern of food intake of a particular individual in daily life. The main purpose of this study was to determine the dietary habits and nutrition knowledge among athletes and non-athletes in National University of Malaysia (UKM). This study was also aimed to determine the relationship between the body mass index (BMI), dietary habits and nutrition knowledge. The total number of respondents was 200 people with 100 athletes were selected from 7 types of sports and 100 non-athletes were selected at random from non-athletes in UKM. Anthropometric measurement included height and weight. Questionnaire was used to assess the socio demographic variables, nutrition knowledge and dietary habits. The results showed that the mean score of dietary habits for athletes (48.9±5:08) was significantly lower, compared to non-athletes (50.4±4.35) (p0.05) than non-athletes (83.5±6:23). The main sources of nutrition information for athletes was from the internet (82%), newspapers or magazines (70%), families or friends or neighbours (65%), television (60%) and coaches (52%). This was quite similar to non-athletes but they did not choose coaches as a source of information. The BMI of athletes and non-athletes did not show a significant relationship with dietary habits and nutrition knowledge. However, it was found that there was a weak significant positive relationship between nutrition knowledge and dietary habits of athletes (r = 0.328, p